Vitamin D Status in Hypothyroid Patients (Bangladesh Medical Journal, 2023)
Vitamin D deficiency is a global health problem. It is estimated that about 25-50% of patients commonly encounter vitamin D deficiency in clinical practice. Recent studies show hypothyroid patients suffer from significantly low vitamin D level. As vitamin D and thyroid hormone act through steroid receptors, one can affect the other’s action. Considering the scientific evidence, the study was aimed to assess the vitamin D level among the subjects with hypothyroidism. This hospital-based case-control study was conducted among 70 subjects including 35 cases and 35 controls at the Departments of Medicine and Endocrinology in Dhaka Medical College Hospital in 6 months duration following approval of this protocol. Data were collected by face to face interview, using a structured questionnaire and case record review. Hospital records including laboratory reports were also reviewed.  Thirty-five cases and thirty-five control samples were screened for vitamin D levels. Data analysis was done using Statistical Package for Social Sciences (SPSS) version 23. Among the participants, 55 were female with a male-female ratio of 1: 3.67. The mean age was 44.6 ± 11.69 year. The highest number of patients were in between 41 to 55 year (41%). The majority of cases were from rural areas (67.0%). There was no significant differences in socio-demographic profiles between the cases and control groups (P >0.05). Hypovitaminosis D was found in 67% of cases. Among them 39.0% had mild insufficiency (20-29 ng/ml), 21.0% had moderate deficiency (10-19 ng/ml) and 7.0% had severe deficiency (< 10 ng/ml). The mean vitamin D level was 23.79 ± 8.1 ng/ml. Serum 25(OH)D level was markedly reduced in hypothyroid cases in comparison to the euthyroid control group [22.14 ± 8.02  and 26.22 ± 7.53 respectively ); P < 0.005]. Data showed hypothyroid patient is likely to develop Hypovitaminosis D 3.37 times higher compared to a euthyroid patient (OR=3.37; 95% CI:1.644-9.7440; P=0.02). Moreover, this lower level is not associated with the difference in age, sex and occupation (P< 0.005). Hypovitaminosis D is associated with hypothyroidism with no variation in respect to age, sex and occupation. The hypovitaminosis D is significantly associated with hypothyroi- dism in the study population.Bangladesh Med J. 2021 Sept; 51(1): 25-32